Adolescência e violência: um desafio para o processo de ensino aprendizagem - Rocha, Katia Cristina Santana (2010)
There are considerable increase in the number of cases of children and adolescents who suffer sexual violence and demonstrate difficulties in the acquisition of the repertoire of reading and writing. So it is necessary new methodologies to assist the professor in teaching process, of this repertoire, the base for the acquisition of others academic repertoires as insure it in the social context. Amongst the different boarding that study the reading, Behavior Analysis comes considering the education of relations between different modalities of stimulations (sound-text-figure) being based on the paradigm of the equivalence of stimulations, by means of the choice procedure in accordance with the model. The present study it had as objective to evaluate the repertoire of reading of children and adolescents victims of sexual violence, elaborating a programming of education with educative software Mestre®. Ten children and adolescents had participated of the researches that were being followed for the Service of Confrontation the Violence in the Great Beach City. The procedure was carried through in three stages: 1) Evaluation of the previous repertoire of reading, focusing relations between the different modalities of stimulations. 2) Application of the programming of education of relations CC, AB, AC, BC, CB, CE, BE and AE and test of the expressive reading (relation C D) of composed words for simple syllables and complexas.3) Test of generalization of Reading of words and composed new phrases for simple and complex syllables. After the education procedure, was verified that the performance of the participants improved considerably, mainly taking in account the small time of trainings and sessions the one that the participants had been submitted. Concluding that the use of software the Mestre® revealed an efficient tool for the reading education